The title of Totonicapán - Christenson, Allen J., translator; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
This work is the first English translation of the Title of Totonicapán, an important document composed by the K'iche' Maya in the highlands of Guatemala in 1554. This volume contains a new translation from the original text, based on a manuscript copy rediscovered by Robert Carmack in 1973.--Provided by publisher.
Transcription, translation, and commentary by Allen J. Christenson.
Keywords: Quiché Indians -- Social life and customs; Quiché Indians -- History; Quiché language -- Texts; Totonicapán (Guatemala) -- History